Pension prefunding, ageing, and demographic uncertainty - Jukka Lassila; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2000)
Pension prefunding can be used to smoothe contribution rates in economies where ageing will increase pension expenditure. But how extensive should prefunding be, in a defined benefit pension system, when there is considerable uncertainty concerning future mortality, fertility, and migration? We study the prefunding rules in the Finnish earnings-related pension system with an OLG simulation model. Increasing the degree of prefunding could yield a more even intergenerational outcome and make future generations' position better, but it is quite possible to overshoot and harm current generations too much. Making the degree of prefunding fertility-dependent seems a useful alternative. With declining fertility, current large cohorts would pay modestly increased contributions. The accumulated funds, however, will be huge in relation to the wage bills of smaller future cohorts. – Pensions ; partial prefunding ; ageing ; demographic uncertainty – – Tavoitteena on tutkia, miten työeläkkeiden rahastoinnilla ja rahastojen käytöllä voidaan vaimentaa väestön ikääntymisen aiheuttamaa eläkemaksujen nousupainetta. Lähtökohtana on nykyinen Suomen yksityisen sektorin työeläkejärjestelmä. Rahastopolitiikan arviointikriteereinä käytetään vaikutuksia kansantaloudellisiin muuttujiin, työnantajan ja työntekijän eläkemaksuihin, eläkejärjestelmän oikeudenmukaisuuteen ja kotitalouksien hyvinvointiin. Tulosten mukaan rahastoinnin kasvattaminen nyt, kun työvoiman määrä on vielä suuri, olisi hyvä tapa tasata väestön ikääntymisen kustannuksia eri sukupolvien kesken. Erityisen suositeltavaa lisärahastointi on silloin, jos ikääntyminen on odotettua nopeampaa. – työeläkejärjestelmä ; rahastointi ; ikääntyminen ; väestöepävarmuus
Keywords: 330; Rentenfinanzierung; Theorie; Finnland; Alternde Bevölkerung